CLIMATE CHANGE EDUCATION INTEGRATION INTO NATURAL SCIENCE CURRICULA OF GENERAL SECONDARY SCHOOLS: ANALYSIS OF A SCIENTIFIC–PRACTICAL SEMINAR - Umaraliyeva M. T.; Haytbayeva S. R.; Abduraxmanova I. Y. (Bright Mind Publishing, 2026)
This article analyzes the content, working process, and scientific–practical significance of the Republic-level seminar titled “Review and approval of recommendations on integrating climate change education into the curricula of natural and exact sciences—biology, chemistry, physics, geography, and mathematics—of general secondary schools in the Republic of Uzbekistan,” held in Tashkent on December 18–19, 2025. The seminar was organized in cooperation with the United Nations Development Programme (UNDP), the “Education Above All” Foundation, the Ministry of Preschool and School Education of the Republic of Uzbekistan, and the “Zamin” International Public Foundation, and is assessed as an important milestone aimed at the systematic introduction of climate change education in Uzbekistan. The article considers, from a scientific–practical perspective, the issues of integrating climate change education into the biology, chemistry, physics, geography, and mathematics curricula of general secondary schools, the model for  teacher preparation and retraining, as well as opportunities to develop students’ “green” skills and leadership capacities. The approaches discussed during the event are analyzed in alignment with the PISA 2029 climate literacy competencies, and methodological and systemic recommendations for subsequent stages are developed. The results substantiate effective implementation of climate change education through the natural science system, improvement of curriculum content, and orienting the educational process toward the Sustainable Development Goals.
Keywords: Climate change education, natural sciences, interdisciplinary integration, PISA 2029, green skills, teacher professional development.